In the Ear of the Beholder: Self-Other Agreement in Leadership Communication and Its Relationship With Subordinates' Job Satisfaction. (October 2019) - Erben, Julian; Schneider, Frank M.; Maier, Michaela
This article deals with the question of how agreement or disagreement in the perception of leadership communication from the perspective of both leader and subordinate is related to subordinates' job satisfaction. Employees of a department in a large, globally operating insurance company and their managers ( N = 110) completed questionnaires including instruments to assess leadership communication from the perspective of the managers and their respective employees as well as employees' job satisfaction. Results from polynomial regression with response surface modeling suggest that there is a positive linear relationship between self- and other ratings of leadership communication and subordinates' job satisfaction, in which the highest scores of job satisfaction are related to high in-agreement ratings of leadership communication. In addition, discrepancies in perceptions of leadership communication decrease job satisfaction, particularly when leaders are overestimators.